Pengaruh konsentrasi ekstrak bawang merah (Allium cepa L.) terhadap pertumbuhan setek nilam (Pogostemon cablin Benth.) - Hizbul Wathan; Nurhayati Bugis; Zuyasna (Program Pascasarjana Universitas Papua, 2022)
This study aims to determine the response to the use of varieties and concentrations of shallot extract and the interaction of these two factors on the variables of patchouli cuttings. This research has been carried out at the Experimental Garden of the Faculty of Agriculture and the Laboratory of Plant Physiology, Faculty of Agriculture Universitas Syiah Kuala, Banda Aceh. The research design used was a 2 x 5 factorial randomized block design (RAK). There were two factors studied, the patchouli variety (Tapak Tuan and Lhokseumawe) and the concentration of shallot extract with 5 levels (0, 15, 30, 45 and 60 ml L-1). The data was analysed using ANOVA and followed by Tukey’s HSD test (Tukey’s Honestly Significant Difference Test) at the level 0.05%. The results showed that the variety affected the number of leaves at 60 and 75 DAP, stem diameter at 75 and 90 DAP, number of shoots at 15, 45, 60 and 90 DAP and shoot height at 15 DAP. The best treatment was the Lhokseumawe variety at a concentration of 60 ml L-1 shallot extract. There was no interaction between the use of the two varieties and the concentration of shallot extract at all parameters of patchouli cuttings observed.